2017
DOI: 10.1371/journal.pmed.1002444
|View full text |Cite
|
Sign up to set email alerts
|

HIV pre-exposure prophylaxis and early antiretroviral treatment among female sex workers in South Africa: Results from a prospective observational demonstration project

Abstract: BackgroundOperational research is required to design delivery of pre-exposure prophylaxis (PrEP) and early antiretroviral treatment (ART). This paper presents the primary analysis of programmatic data, as well as demographic, behavioural, and clinical data, from the TAPS Demonstration Project, which offered both interventions to female sex workers (FSWs) at 2 urban clinic sites in South Africa.Methods and findingsThe TAPS study was conducted between 30 March 2015 and 30 June 2017, with the enrolment period end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
191
5

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 137 publications
(209 citation statements)
references
References 17 publications
13
191
5
Order By: Relevance
“…The cost‐effectiveness results should be viewed as illustrative and interpreted with extreme caution since unit cost estimates were not derived from country‐specific primary costing exercises and did not reflect any differences in implementation models that might influence costs between the countries and across populations served. The PrEP unit costs used in this study (ranging from US$106–US$236) are somewhat higher than those previously reported (USD$87–$144) , due to differences in implementation models studied and cost categories included in the different costing studies. In addition, we included optimistic assumptions for the effectiveness of and adherence to PrEP.…”
Section: Discussioncontrasting
confidence: 58%
“…The cost‐effectiveness results should be viewed as illustrative and interpreted with extreme caution since unit cost estimates were not derived from country‐specific primary costing exercises and did not reflect any differences in implementation models that might influence costs between the countries and across populations served. The PrEP unit costs used in this study (ranging from US$106–US$236) are somewhat higher than those previously reported (USD$87–$144) , due to differences in implementation models studied and cost categories included in the different costing studies. In addition, we included optimistic assumptions for the effectiveness of and adherence to PrEP.…”
Section: Discussioncontrasting
confidence: 58%
“…Notions of risk compensation were not common among the actual use studies in this review, and reported sexual behaviour did not change over time in any of the efficacy trials or demonstration projects . However, this has continued to be a concern expressed from higher level stakeholders.…”
Section: Discussionmentioning
confidence: 90%
“…A promising option is the introduction of multipurpose HIV prevention products, co‐formulated or co‐packaged combinations of HIV, STI, and/or contraceptive compounds, which have been estimated to be cost‐effective among FSWs in South Africa (Quaife et al, ). In addition, PrEP use may increase FSW contact with the health system as women collect monthly or three‐monthly prescriptions (Eakle et al, ). The South African national guidelines for PrEP implementation indicate that syndromic STI screening will be carried out at each visit, alongside HIV testing and behavioral sexual risk reduction counseling, whereas a urine pregnancy test will be carried out at PrEP initiation (Department of Health South Africa, ).…”
Section: Discussionmentioning
confidence: 99%